System dynamics mechanism of cross-regional collaborative dispatch of emergency supplies based on multi-agent game - Ying Qiu; Meng Shi; Xinna Zhao; Yongping Jing (Complex & Intelligent Systems, 2021)
Abstract The cross-regional coordinated dispatch of emergency supplies is a complex issue involving multiple topics, which covers multiple relationships and is affected by multiple variables. In the face of severe emergencies, relief supplies inside a specific area are far from meeting the explosive demand for emergency supplies. Besides, the supply of emergency materials and the disaster areas often have a spatial mismatch. Considering the attributes of externalities and public goods of emergency rescue, there are many obstacles for Local administration of emergency (LAE) and emergency logistics enterprises (ELE) spontaneously carrying out emergency supplies across regions. To solve this complexity problem, this research abstracts higher-level administration of emergency (HAE), LAE and ELE as the main stakeholders, with which a tripartite evolutionary game (ETG) model and a system dynamic (SD) model are constructed to analyze the dynamic mechanism of the complex system and to carry out the numerical simulation of the three-party game process. All the analyses and tests in this study have proved that the strong supervision of HAE has a decisive impact on the realization of cross-regional coordinated dispatch of emergency supplies, and the financial rewards and punishments imposed by HAE on other entities can accelerate or delay the achievement of the equilibrium strategy. However, when HAE chooses not to regulate, the cooperation willingness of LAE affects a lot that all the stakeholders will eventually reach equilibrium at (1,1,1) only if LAE chooses to actively carry out cross-regional coordinated dispatch of emergency supplies.